The Transformation of Japanese Employment Relations Reform without Labor - Imai, J.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2011)
This book systematically evaluates the impacts of deregulatory reforms on employment relations in Japan especially focusing on the core white collar workers. Concentrating on changes in three aspects of employment relations; contracts, employee mobility and worker effort, it examines the process of social negotiation and its results.
Keywords: International business enterprises; Personnel management; International economics; International Business; Human Resource Management; International Economics